Examination of Cholesterol Levels in the Community of Panyileukan District, Bandung City - Lia Mar’atiningsih; Sugiah Sugiah; Astari Nurisani (Jurnal Pengabdian Bidang Kesehatan, 2024)
Hypercholesterolemia is a term when total cholesterol, LDL, and triglyceride levels increase, while HDL decreases. The causes of high cholesterol today are poor diet, suboptimal physical activity, excessive caffeine consumption, and uncontrolled body weight. The purpose of this community service is to increase public knowledge about hypercholesterolemia, including its causes, symptoms, and treatment. In addition, cholesterol examinations were also carried out on 25 residents using the POCT method.